KAJIAN EKSPERIMEN PENGARUH PEMASANGAN SILINDER SIRKULAR DENGAN DIAMETER SILINDER 16 CM DAN JARAK 20 CM PADA SISI ADVANCING BLADE TURBIN AIR SAVONIUS - Deni Purnanto; Subagio Soim; Priyo Agus Setiawan (Politeknik Perkapalan Negeri Surabaya, 2020)
Savonius turbine for the first time was founded by Sigurd Johannes Savonius in 1922. This turbine hasvertical axis and half-round shaped on each side of blades and like an “S”. This turbine aslo called as drag turbinebecause it need drag force on its blades to whirling the turbine. Many research were done to increasing theperfomance of this turbine and one of them was using deflector plate in front of the turbine. On this experiment,the method is using distance and diameter of circular cylinder variations. The turbine for this experiment usingmyring equation with n=1 for the blades shape. Dimension of the turbine is 400 mm in height and 400 mm indiameter. The diameter of circular cylinder (ds) is 16 cm and the distance (A) is 20 cm used in this experiment.The result obtained in this experiment showing that the highest value of Ct is 0,3038 at TSR 0,633 with increasedpercentage is 7,955%. The highest Cp value is 0,1924 at TSR 0,633 with increased percentage is 20,828%.